Development of an Integrated Industry-Based Learning Model to Improve Electric Vehicle Learning Tools Work Readiness of Vocational Students - Fanani Arief Ghozali; Bambang Sudarsono; Fatwa Tentama; Surahma Asri Mulasari; Tri Wahyuni Sukesi; Sulistyawati Sulistyawati; Herman Yuliansyah; Lu'lu' Nafiati; Adelia Saharani; Prabandari Listyaningrum (VANOS Journal of Mechanical Engineering Education, 2023)
Vocational schools need to start addressing unemployment right away since it is a serious issue. Work readiness is prepared with the demands of the industrial world in mind. The objective of this study is to create and evaluate industry-based integrated learning models for EVL+i, or electric vehicle auxiliary, subjects. The research and development (R&D) design used was Richey and Klein's design. This research involved 34 students, 6 teachers from the automotive engineering department of SMK Muhammadiyah 2 Tempel, and 4 professionals from the automotive industry. Practical performance tests and interviews were used as data collection methods. Based on the research results, it can be said that the EVL+i model was successfully developed and implemented in three stages of research. The EVL+i model can improve 6 aspects of competence of automotive vocational students, namely aspects of integrity competence, cooperation, discipline, work area knowledge, work completeness and time efficiency. The six aspects of competence have increased from the category of less good to very good with an average score of 1.82 in the limited trial and 3.72 in the extended trial.